Sheehan's syndrome: A rare cause of delayed recovery after anesthesia - Garima Choudhary; Shikha Soni; Sadik Mohammed (Wolters Kluwer Medknow Publications, 2020)
Sheehan's syndrome (SS) or adenohypophyseal insufficiency is a rare but known complication of postpartum hemorrhage (PPH). It develops as result of ischemic pituitary necrosis secondary to a brutal and extended shock due to obstetric hemorrhage. The clinical presentation of this syndrome is variable and marked with abrupt or insidiously developing pituitary insufficiency. We report a case of 35-year-old female scheduled for laparoscopic appendicectomy under general anesthesia who developed delayed recovery. Proper history revealed that patient had history of severe PPH and was amenorrheic after that for last 4 years. Investigation revealed that pan hypopituitarism and neuroimaging (magnetic resonance imaging) showed reduced pituitary size. Replacement of deficient hormone leads to recovery and weaning from mechanical ventilation.